Imaginary plots and political realities in the plays of William Congreve - Novak, Maximillian E. (Anthem Press, 2020)
Imaginary Plots and Political Realities in the Plays of William Congreve is a study of the political and social milieu that informs William Congreve's writings. The book attempts to read Congreve's plays and his novella, Incognita, against the political and social upheaval of the period initiated by the rebellion of 1688.